2016
DOI: 10.1152/ajplung.00122.2015
|View full text |Cite
|
Sign up to set email alerts
|

Increased TGF-β: a drawback of tracheal occlusion in human and experimental congenital diaphragmatic hernia?

Abstract: Survivors of severe congenital diaphragmatic hernia (CDH) present significant respiratory morbidity despite lung growth induced by fetal tracheal occlusion (TO). We hypothesized that the underlying mechanisms would involve changes in lung extracellular matrix and dysregulated transforming growth factor (TGF)-β pathway, a key player in lung development and repair. Pulmonary expression of TGF-β signaling components, downstream effectors, and extracellular matrix targets were evaluated in CDH neonates who died be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 66 publications
4
13
1
Order By: Relevance
“…Vukovich, et al reported both elastogenesis and transforming growth factor-β signaling were increased in DHTO to levels beyond those of DH or control (6,7). Again, our findings regarding these processes did not reach statistical significance; however their findings are consistent with the observed pattern that processes impacted by DH are excessively reversed in DHTO.…”
Section: Acknowledgmentssupporting
confidence: 51%
See 1 more Smart Citation
“…Vukovich, et al reported both elastogenesis and transforming growth factor-β signaling were increased in DHTO to levels beyond those of DH or control (6,7). Again, our findings regarding these processes did not reach statistical significance; however their findings are consistent with the observed pattern that processes impacted by DH are excessively reversed in DHTO.…”
Section: Acknowledgmentssupporting
confidence: 51%
“…While TO for CDH may gain more widespread acceptance in the coming years, there remains an urgent need to understand the cellular responses to CDH and TO so that targeted therapies may be developed to improve fetal lung development and to limit any undesirable effects of TO. There have been reports of how CDH and TO impact lung matrix synthesis (6)(7)(8)(9), lung epithelial function and surfactant (10)(11)(12)(13) and microvascular development (14)(15)(16), and that tracheal occlusion reverses some of resulting in severe pulmonary hypoplasia (2). Despite optimal medical and surgical care, mortality remains high with survivors experiencing severe restrictive lung disease and significant pulmonary hypertension (1).…”
mentioning
confidence: 99%
“…In the lamb model of CDH (GD80; term = 145; late pseudoglandular), there was upregulation of TGF‐β2 following TO (GD110; canalicular), both at the protein and RNA levels, with no concomitant increase in TGF‐β1. In the rabbit model, Vuckovic et al found an upregulation of mRNA expression of TGF‐β2 yet TGF‐β2 peptide levels could not be quantified . Likewise, we found no differences in protein expression of TGF‐β2 in hypoplastic lungs in either the late canalicular or alveolar stages of lung development.…”
Section: Discussioncontrasting
confidence: 67%
“…We previously demonstrated that hypoplastic human lungs have decreased TGF‐β2 expression in the alveolar stage of lung development . A larger series of human lungs between 21 and 39 weeks of gestation failed to show major differences in protein expression between any of the isoforms of TGF‐β in control and DH lungs . In the lamb model of CDH (GD80; term = 145; late pseudoglandular), there was upregulation of TGF‐β2 following TO (GD110; canalicular), both at the protein and RNA levels, with no concomitant increase in TGF‐β1.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation